Understanding Polarization Effects on Voice-Based Social Media: A Clubhouse Analysis - Caroleo, Laura; Maiello, Giuseppe (Italian Sociological Review, 2022)
Modern societies have been strongly influenced by the development of digital media, which has facilitated not only the transmission of information and symbolic content, but also the creation of new forms of action, interaction, and social relations. The pervasiveness of digitization increased between 2020 and 2021 due to the COVID-19 pandemic, which led to the lockdown of the entire world population and moved sociality predominantly online. The year 2020 also saw the emergence of a new social media platform called Clubhouse, which was based entirely on oral communication. The “global village” is recovering what Walter Ong calls secondary orality, which is typical of electronic media in literate societies, characterized by the recovery of speech in electronic form. Today, the development of technologies has introduced what Derrick de Kerckhove calls tertiary orality. The objective of this article is to follow the re-emergence of oral cultures as a new mode of online communication, focusing on the Italian community and the divergence between different groups of users strictly associated with polarization in highly propagandistic discourse.